2012
DOI: 10.1002/adsc.201200362
|View full text |Cite
|
Sign up to set email alerts
|

Application of Tethered Ruthenium Catalysts to Asymmetric Hydrogenation of Ketones, and the Selective Hydrogenation of Aldehydes

Abstract: , 1974-and Wills, Martin. (2012 Application of tethered ruthenium catalysts to asymmetric hydrogenation of ketones, and the selective Hydrogenation of aldehydes. Advanced Synthesis & Catalysis, 354 (13). pp. 2545-2555. Permanent WRAP url:http://wrap.warwick.ac.uk/55017 Copyright and reuse:The Warwick Research Archive Portal (WRAP) makes this work by researchers of the University of Warwick available open access under the following conditions. Copyright © and all moral rights to the version of the paper present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 98 publications
2
56
0
Order By: Relevance
“…Improved synthetic approaches to 2 ( n = 1) 7,8a require conversion of the alcohol from step (i) to the tosylate, triflate, or mesylate and coupling with the diamine component, and also combine the last two stages into one. In alternative approaches, a [4 + 2] cycloaddition may be employed to form the required diene.…”
mentioning
confidence: 99%
“…Improved synthetic approaches to 2 ( n = 1) 7,8a require conversion of the alcohol from step (i) to the tosylate, triflate, or mesylate and coupling with the diamine component, and also combine the last two stages into one. In alternative approaches, a [4 + 2] cycloaddition may be employed to form the required diene.…”
mentioning
confidence: 99%
“…These results confirmed the advantage of the tethered catalyst design already reported in the area of chiral catalysis. [8,9] The improved results are probably a consequence of increased catalyst robustness in the presence of poly-functionalised substrates.…”
Section: Resultsmentioning
confidence: 97%
“…[9] Initial tests indicated that different reducing agents were effective: formic acid/triethylamine (5:2 and 1:1 mixtures) as well as sodium formate and ammonium formate in a biphasic system of EtOAc/water. The biphasic system was found to be particularly convenient to facilitate workup and product isolation and rapidly allowed the reduction of the catalyst loading from S/C (equivalents S = substrate/C = catalyst) 1000:1 (Table 1, entry 1) to S/C 5000:1 (entry 2) and S/C 10 000:1 (entry 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 In a relatively recent development, tethered ruthenium catalysts (such as those in eq 22) have proven highly effective for the asymmetric reduction of ketones and for selective reduction of aldehydes. 51 Iron catalyzed hydrogenation of ketones is currently under development in an effort to move away from the platinum group metals (due to their cost, low abundance, and toxicity). 52,53 Mechanistically, this takes place through coordination of the ketone to a dearomatized iron center, insertion into the created Fe-H bond, followed by readdition of hydrogen to regenerate the active catalyst.…”
Section: Carbon-carbon Bond Reductionsmentioning
confidence: 99%